2019
DOI: 10.14527/pegegog.2019.031
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability study of Effects of Digital Games in Early Ages Scale

Abstract: The aim of this research is to develop a scale aiming to measure the effects of digital games on children during early childhood period according to parent perceptions. In the course of developing the scale items, related literature was reviewed in detail and relevant scales and the previous research carried out were examined. After the expert opinions were obtained, the scale was sent to the families of 1500 children by administrators and teachers who worked in the primary schools and kindergartens, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…There are no studies in the literature to develop tools to directly measure digital play addiction for children in early childhood. Similar studies focused on the early childhood period examined the children's digital play habits and app usage (Kanak & Özyazıcı, 2018), the parental digital play preferences (Işıkoğlu-Erdogan et al, 2019) and validation of scales related to the effects of digital play (Balaban-Dağal & Bayındır, 2019). The scale items developed in this study were developed with the Lemmens et al (2009) study in mind, as well as with the developmental characteristics of early childhood children in mind.…”
Section: Addiction and Digital Play Addictionmentioning
confidence: 98%
“…There are no studies in the literature to develop tools to directly measure digital play addiction for children in early childhood. Similar studies focused on the early childhood period examined the children's digital play habits and app usage (Kanak & Özyazıcı, 2018), the parental digital play preferences (Işıkoğlu-Erdogan et al, 2019) and validation of scales related to the effects of digital play (Balaban-Dağal & Bayındır, 2019). The scale items developed in this study were developed with the Lemmens et al (2009) study in mind, as well as with the developmental characteristics of early childhood children in mind.…”
Section: Addiction and Digital Play Addictionmentioning
confidence: 98%
“…Internal consistency coefficients of the factors are .82 for fun dimension, .90 for learning, .86 for physical, .87 for social, and .84 for emotional dimension. The analyses conducted have shown that the "Scale of the Effects of Digital Games at Early Years", which consists of 25 items, is a valid and reliable scale.Cronbach Alpha coefficients were calculated to test the reliability of the sub-factors of the instruments in the study group(Balaban Dağal & Bayindir, 2019). Alpha index results are in…”
mentioning
confidence: 99%